Relatório de Estágio Programas de Treino de Força e Multicomponente para Idosos - José Pedro Pereira Silva Cunha (2020)
This internship report was integrated in the 2nd year of the 2nd Cycle in Physical Activity for Elderly at the Faculty of Sports of University of Porto. This report aims to describe and reflect on the practical work done in the 2019-2020 school year. This document includes the planning, application and reflection of the activities involved in the training process of six groups of older adults: i) a strength training group for autonomous and independentolder adults, ii) three multicomponent training group for autonomous and independent older adults; and iii) two groups of multicomponent training for the older adults with dementia. The training sessions took place at the Faculty of Sports of the University of Porto and at "Os Físicos" in Senhora da Hora. The training programs were based on the recommendations of physical exercise for the elderly. All seniors were assessed at the beginning and end of the training year (October and June) for physical fitness according to the Senior Fitness Test protocol. The effects of training programs were observed through descriptive statistics (mean and standard deviation) and non-parametric hipothesis test (Wilcoxon).